STOCK MARKET SEGMENTATION IN CHINA AND ANALYSIS OF ITS DETERMINANTS - Li, Haotian (2016)
In China, the A-share markets (available mainly to domestic investors) and the B- or H-share markets (available mainly to foreign investors) form a mildly segmented stock market structure with the characteristic of difference between A- and B- or H-share prices for the same dual-listing company. Contrary to stock markets in other countries or areas with a segmentation structure, Chinese A shares are traded at a premium relative to their B- or H-share counterparts. In this article, price difference between A and H shares in two stock exchanges, the Shanghai Stock Exchange (SHSE) and the Shenzhen Stock Exchange (SZSE), is described, and its determinants are examined by regression analysis with panel data and a series of tests. From the findings, it can be seen that information asymmetry and demand elasticity significantly affect price difference in both stock exchanges, while the firm size effect operates only in SHSE.